Considering critical methods and theoretical lenses in digital religion studies. (January 2017) - Lövheim, Mia; Campbell, Heidi A
This article introduces a special issue on critical methods and theoretical lenses in Digital Religion studies, through contextualising them within research trajectories found in this emerging field. By starting from the assertion that current "fourth-wave of research on religion and the Internet, " is focused on how religious actors negotiate the relationships between multiple spheres of their online and offline lives, article authors spotlight key theoretical discussions and methodological approaches occurring within this interdisciplinary area of inquiry. It concludes with notable methodological and theoretical challenges in need of further exploration. Together it demonstrates how religion is practiced and reimagined within digital media spaces, and how such analysis can contribute to broader understanding of the social and cultural changes new media technologies are facilitating within society.